Lovinskaya A.V., Kolumbayeva S.Zh., Esim Zh.I., Voronova N. The antimutagenic potential of extracts from Limonium gmelinii family Plumbaginaceae (= Limoniaceae Lincz.): Al-Farabi Kazakh National University, Kazakhstan, Almaty, *e-mail: annalovinska@rambler.ru - Kolumbayeva S.Zh., Esim Zh.I., Voronova, Lovinskaya A.V. (Eurasian Journal of Ecology, 2018)
The cytogenetic and mutagen-modifying activity of a complex of biologically active substances in extracts from shoot and root parts of Limonium gmelinii were investigated testing on count chromosome abnormalities of cells of barley root meristem. Plant extracts in concentrations 50.0 and 100.0 mg/L have no mutagenic activity, but, on the contrary, reduced the level of spontaneous mutagenesis. As a result of the combined effect of methanesulfonate mutagen (MMS) and plant extracts, a statistically significant decrease in the level of MMS-induced mutagenesis was observed. Extracts of BAS from the shoot and root parts of L. gmelinii in all concentrations and all variant of treatment have strong antimutagenic activity against MMS. The maximum antimutagenic effects were observed during BAS preliminary treatment MMS exposure and were 64.70% and 67.46% for the root and shoot parts, correspondingly. The mitotic index (MI) of the root meristem of germinating seeds, separately and jointly treated with MMS and extracts, was studied. Plant extracts gave a mitostimulatory effect, while MMS significantly reduced the proliferative activity of the root meristematic cells as compared to the control. Pre- and post- treatment of BAS from the shoot and root parts statistically significantly increased the mitotic activity of the root meristem in comparison with MMS. Genoprotective action of these BASs can be due to their ability to inhibit free radical processes, enhanced by the action of various genotoxicants, and to stimulate chromosome repair. Herbal preparations can be considered the most promising as therapeutic agents aimed at leveling the action of mutagens on the body. Key words: Limonium gmelinii, biologically active substances, antimutagen, chromosome aberrations, mitotic index.